Molecular phylogenetics and evolutionary history of the endemic land snail genus Everettiain northern Borneo - Liew, Thor Seng; Marzuki, Mohammad Effendi; Schilthuizen, Menno; Chen, Yansen; Vermeulen, Jaap J.; Mohd-Azlan, Jayasilan (PeerJ (O'Reilly and SAGE), 2020)
Borneo has gone through dramatic changes in geology and topography from theearly Eocene until the early Pliocene and experienced climatic cycling during thePleistocene. However, how these changes have shaped the present-day patterns ofhigh diversity and complex distribution are still poorly understood. In this study, weuse integrative approaches by estimating phylogenetic relationships, divergence time,and current and past niche suitability for the Bornean endemic land snail genusEverettiato provide additional insight into the evolutionary history of this genus innorthern Borneo in the light of the geological vicariance events and climaticfluctuations in the Pleistocene. Our results show that northern BorneoEverettiaspecies belong to two deeply divergent lineages: one contains the species that inhabithigh elevation at the central mountain range, while the other contains lowlandspecies. Species diversification in these lineages has taken place before the Pliocene.Climate changes during the Pleistocene did not play a significant role in speciesdiversification but could have shaped contemporary species distribution patterns.Our results also show that the species-rich highland habitats have acted as interglacialrefugia for highland species. This study of a relatively sedentary invertebrate supportsand enhances the growing understanding of the evolutionary history of Borneo.Species diversification inEverettiais caused by geological vicariance events betweenthe early Miocene and the Pliocene, and the distribution patterns were subsequentlydetermined by climaticfluctuations in the Pleistocene.